The Effect o f Planting Media And Organic Fertilizer Urine Cow On Growth Pepper Seedlings ( Piper Nigrum L.) Malonan Variety 1: PENGARUH MEDIA TANAM DAN PUPUK ORGANIK CAIR URIN SAPI TERHADAP PERTUMBUHAN BIBIT LADA ( Piper nigrum L . ) VARIETAS MALONAN 1 - Mahdalena; Tutik Nugrahini; Rosalina Mebang (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Research on application of solid decanter and SP 36 fertilizer on vegetative growth of palm oil seeds (Elaeis guineensis Jacq) age 1 month. The study was conducted for 12 weeks (3 months) from May - August 2021. The research was carried out in the Agrotechnology Experimental Garden at Widya Gama Mahakam University Samarinda. This research uses The research method used a Randomized Block Design (RAK) with a 4 x 4 factorial experiment consisting of 3 replications. The first factor is P0 = No Treatment (Control), P1 = 75g/polybag, P2 = 100g/polybag, P3 = 125g/polybag. While the second factor is SP-36 fertilizer with: S0 = No Treatment (Control), S1 = 1.5g/polybag, S2 = 2.5g/polybag, S3 = 3.5g/polybag. The expected output is to provide information about the best dose of solid decanter for vegetative growth of falm oil for the community. Provide information about the best SP 36 fertilizer for the vegetative growth of palm oil for the community.